(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Indian poetry has a deep and prosperous history dating back to ancient times. Poetry in foreign languages such as Persian and English also has a powerful force on Indian poetry. The poetry reflects distinct metaphysical custom within India. In particular, many Indian poets have been inspired by magical experiences. Poetry is the oldest form of literature and has a rich written and oral tradition. The primitive period in India saw the evolution of various great poets which include Rahim, Kabir and Tulsidas. Tulsidas, in particular, wrote Ramcharitmanas which has been acclaimed as “The tallest tree in the magic garden of medieval Indian poetry”. Nineteenth and twentieth century has seen the emergence of several towering figures in Indian literature which include Mirza Ghalib, Rabindranath Tagore, Sarojini Naidu, Mahadevi Verma and Kamala Das.